The chloroplast genome of the pincushion cactus Mammilllaria haageana subsp. san-angelensis, a Mexican endangered species - Silvia Hinojosa-Alvarez; Salvador Arias; Sylvie Ferrand; Michael D. Purugganan; Julio Rozas; Ulises Rosas; Ana Wegier (Mitochondrial DNA. Part B. Resources, 2020)
The genus Mammillaria occupies diverse habitats and exhibits diverse growth patterns and a large range of morphologies. Most of the species of this genus are used as ornamental plants and are subject to mass habitat loss. Due to these factors, they are being submitted to selective pressure that might affect conservational efforts and management plans. We obtained the 133 gene chloroplast genome as part of the project of sequencing the complete genome of pincushion cactus, including 88 protein-coding genes, 8 rRNA genes, and 37 tRNA genes. The phylogenetic tree indicates the pincushion cactus is a sister species of M. supertexta and M. huitzilopochtli.